2021
DOI: 10.3389/fcimb.2021.639665
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Microbiota and Cytokine Levels Predict Preterm Delivery in Asian Women

Abstract: Preterm birth (PTB) is the most common cause of neonatal morbidity and mortality worldwide. Approximately half of PTBs is linked with microbial etiologies, including pathologic changes to the vaginal microbiota, which vary according to ethnicity. Globally more than 50% of PTBs occur in Asia, but studies of the vaginal microbiome and its association with pregnancy outcomes in Asian women are lacking. This study aimed to longitudinally analyzed the vaginal microbiome and cytokine environment of 18 Karen and Burm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 67 publications
(83 reference statements)
9
48
0
Order By: Relevance
“…In previous work, we have observed that the most prevalent vaginal microbiota community compositions in European Caucasian women are those dominated by L. crispatus (50%) followed by L. iners (25%), whereas the inverse has been reported for Asian and Black women ( L. iners , 48% and 50% v L. crispatu s, 26% and 20%, respectively) 6 . Higher frequency of L. iners dominated vaginal microbiota has also been reported in Indian 43 , Karen and Burman 44 , Hispanic and African American pregnant women 9 , 10 , 17 . Our results therefore provide further evidence that ethnic and/or geographical differences are a major source of variation in the underlying structure and composition of the vaginal microbiome during pregnancy.…”
Section: Discussionmentioning
confidence: 57%
“…In previous work, we have observed that the most prevalent vaginal microbiota community compositions in European Caucasian women are those dominated by L. crispatus (50%) followed by L. iners (25%), whereas the inverse has been reported for Asian and Black women ( L. iners , 48% and 50% v L. crispatu s, 26% and 20%, respectively) 6 . Higher frequency of L. iners dominated vaginal microbiota has also been reported in Indian 43 , Karen and Burman 44 , Hispanic and African American pregnant women 9 , 10 , 17 . Our results therefore provide further evidence that ethnic and/or geographical differences are a major source of variation in the underlying structure and composition of the vaginal microbiome during pregnancy.…”
Section: Discussionmentioning
confidence: 57%
“…In previous work, we have also observed that the most prevalent vaginal microbiota community compositions in European Caucasian women are those dominated by L. crispatus (50%) followed by L. iners (25%), whereas the inverse was seen for women self identifying as Asian and Black ( L. iners, 48% and 50% v L. crispatu s, 26% and 20%, respectively)(6). Similarly, higher frequency of L. iners dominated vaginal microbiota has been reported in Indian (39), Karen and Burman (40), Hispanic and African American pregnant women (9,10,17). Our results therefore provide further evidence that ethnic and/or geographical differences are a major source of variation in the underlying structure and composition of the vaginal microbiome during pregnancy.…”
Section: Discussionmentioning
confidence: 55%
“…It may be related to genetic and environmental factors, including geographic location, diet, age, BMI, drug exposure, physical activity, and availability of resources such as access to medical care. However, studies show that the presence of L. iners in the vagina of Asian women does not increase the risk of abnormal pregnancy ( Serrano et al 2019 ; Kumar et al 2021 ).…”
Section: Protective Role Of Lactobacilli In the Vaginamentioning
confidence: 99%